Voluminous Intrapericardial Lipoma Mimicking Pericardial Effusion - Fabíola Prado de Morais; Noah Romero Nakajima; Olívia Félix Marconi Andalécio; Pedro de Santana Prudente; Guilherme Emílio Ferreira; Andrea de Martino Luppi; Fernando Costa Mundim; Olga Maria Lima Aguiar; Juliana Salomão Daud Melo; Bruno de Carvalho Dornelas (Case Reports in Medicine)
Lipomas are rare primary heart tumors and may involve the endocardium, myocardium, or pericardium. Signs and symptoms depend on the tumor location and size. The intrapericardial lipoma we report has massive dimensions and mimics a pericardial effusion. A 38-year-old male complained of dyspnea and precordial pain. On physical examination, heart sounds were diminished. The patient had received extensive medication for a clinically suspected pericardial effusion due to heart failure. A voluminous mass resembling fat within the pericardial sac was revealed by transesophageal echocardiography and a computed tomography scan. The tumor was removed successfully by a subxiphoid surgical approach. The diagnosis of a 635 gram intrapericardial lipoma was confirmed by pathological examination. After surgery, the patient recovered well and was completely asymptomatic at a follow-up at 90 days. No medications were being taken since. The diagnosis of a pericardial effusion should be secured by imaging exams to avoid unnecessary medications. Cardiac lipomas can be readily recognized by their typical features on radiologic imaging. The surgical pathology examination confirms the diagnosis and rules out malignancy criteria.